ANALISIS MODEL LOG LINIER TIGA DIMENSI UNTUK DATA KUALITATIF DENGAN METODE FORWARD - Siti Fatimah Sihotang; Zuhri Zuhri (MES: Journal of Mathematics Education and Science, 2020)
The three-dimensional linear log model is an equation in the form of a model in statistics that is used to describe whether there is a relationship between two or more variables and the pattern of their relationship at the same time to find out which cells cause dependencies. The number of variables discussed in this study was three variables. After the variables are investigated, the formation of a log-linear model becomes important because not all the model factor interactions that exist in the complete model are significant in the resulting model. This study aims to perform linear log modelling to obtain a suitable final model, using the Forward method for case examples of qualitative data. From the examples of cases that have been worked on, it is known that the Forward method is the best model building method because this method is used more as a process of adding one by one the interaction between factors in the model to evaluate the fit of a model. This will provide an alternative choice in determining the best model after going through the fittest for each model that is formed.